PERAN KORBAN ANAK DALAM TINDAK PIDANA KEKERASAN SEKSUAL (PERSPEKTIF HUKUM, KRIMINOLOGI, VIKTIMOLOGI) - Yunus, Ahmad (Fakultas Ilmu Sosial dan Humaniora, 2024)
Crimes of sexual violence against children are still very common, there are many factors that cause this incident. This research examines the role of victims in the occurrence of criminal acts of sexual violence against children from three perspectives, namely a legal perspective, a criminological perspective and a victimological perspective. This research also examines future criminal law policies related to sexual violence against children. This research uses a normative juridical research type (legal research). This type of normative juridical research out by examining various formal is carried legal regulations such as laws and regulations related to the issues discussed. The problem in this research are the approaches used case approach, the statutory approach and the conceptual approach. In this research, there is a vacuum in norms, so the government as a policy maker must review and create new policies related to criminal law, especially regarding criminal acts of violence against sexual children.